Neonatal outcomes and congenital malformations in children born after progestin-primed ovarian stimulation protocol - Li, Danjun; Hu, Zhijie; Chen, Qiuju; Chai, Weiran; Cai, Renfei; Kuang, Yanping; Lu, Xuefeng (Frontiers in Endocrinology, 2022)
Purpose: To assess the safety of progestin-primed ovarian stimulation (PPOS) protocol regarding the neonatal outcomes and congenital malformations in babies born after in vitro fertilization (IVF) and frozen embryo transfer (FET). Methods: In this large retrospective cohort study, a total of 16493 infants born between September 1, 2013 and July 31, 2021 from IVF and FET cycles after treatment with either PPOS (n=15245) or gonadotropin-releasing hormone antagonist (GnRH-ant) (n=1248) were finally enrolled. The primary outcome measure was the incidence of congenital malformations. The secondary outcome measures were rates of low birth weight (LBW), very low birth weight (VLBW), preterm birth (PTB), very preterm birth (VPTB) and early neonatal death. Results: Birth characteristics for both singletons and twins regarding the sex of infants, gestational age, birth weight and birth length were comparable between PPOS group and GnRH-ant group. Rates of LBW, VLBW, PTB, VPTB and early neonatal death were also similar. The re-analysis using propensity score matching (PSM) and multivariable logistic regression indicated that PPOS protocol could not increase the risk of adverse neonatal outcomes compared with GnRH-ant protocol. Furthermore, no significant difference was observed in the overall incidence of congenital malformations in live-born babies. After PSM and controlling for all confounders, the results remained insignificant with an adjusted odds ratio of 0.66 [95% confidence interval (CI) 0.32-1.34] and 2.43 [95% CI 0.97-6.06], respectively for singletons and twins. Conclusions: Our study suggests that compared with GnRH-ant treatment for IVF, PPOS protocol could not produce a negative effect on the newborn population in terms of neonatal outcomes and congenital malformations.